PELATIHAN ADMINISTRASI KEUANGAN KOPERASI DALAM MENDUKUNG PROGRAM KOPERASI MERAH PUTIH - Usmar, Andi; Resa Sania Kamila; Fatma azka Azkia Ma’ruf; Nunung Nurhayati; Fajar Dimas Saputra (PT. Jurnal Center Indonesia Publisher, 2026)
Strengthening the financial administration capacity of cooperatives is a crucial element in supporting the sustainability and accountability of cooperative institutions in Indonesia. This community service activity aims to improve the understanding and skills of cooperative administrators in financial administration through a hybrid Pelatihan (online and offline). This program aligns with the government's